2017
DOI: 10.1007/s11548-017-1559-8
|View full text |Cite
|
Sign up to set email alerts
|

Robust motion tracking in liver from 2D ultrasound images using supporters

Abstract: Purpose: Effectiveness of image-guided radiation therapy with precise dose delivery depends highly on accurate target localization, which may involve motion during treatment due to, e.g., breathing and drift. Therefore, it is important to track the motion and adjust the radiation delivery accordingly. Tracking generally requires reliable target appearance and image features, whereas in ultrasound imaging acoustic shadowing and other artifacts may degrade the visibility of a target, leading to substantial track… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(12 citation statements)
references
References 17 publications
0
12
0
Order By: Relevance
“…With a simple template‐tracking algorithm, the motion of the vessel structure was quantified postacquisition and compared to the EM position signal. Several real‐time tracking algorithms have been developed, but these are optimized for in vivo liver ultrasound data and thus are suboptimal for silicone imaging. Nevertheless, such methods yield average tracking accuracies below 1 mm in under 50 ms lag and therefore are essential in future in vivo applications on patients.…”
Section: Discussionmentioning
confidence: 99%
“…With a simple template‐tracking algorithm, the motion of the vessel structure was quantified postacquisition and compared to the EM position signal. Several real‐time tracking algorithms have been developed, but these are optimized for in vivo liver ultrasound data and thus are suboptimal for silicone imaging. Nevertheless, such methods yield average tracking accuracies below 1 mm in under 50 ms lag and therefore are essential in future in vivo applications on patients.…”
Section: Discussionmentioning
confidence: 99%
“…PDI cannot display the direction and speed of blood flow, as well as direct quantitative values such as resistance index and maximum systolic peak, so it can only be used as a supplement to CDFI [16][17][18]. However, with the in-depth study of CDFI and PDI in musculoskeletal neurological diseases, it has shown good prospects [19,20]. It is believed that high-frequency ultrasound will be an indispensable imaging method for the diagnosis of musculoskeletal neurological diseases in the near future.…”
Section: Related Workmentioning
confidence: 99%
“…In addition to these registration-based methods, optical flow-based approaches rely on the locational correlation of a set of points between the tracking and reference frames. [35][36][37] Kondo et al 38 proposed a method using kernelized correlation filter-based algorithm with extensions of adaptive window size selection and motion vector refinement with template matching. Shepard et al 39 investigated a similarity measurement-based block matching algorithm incorporating training methods and multiple simultaneous templates to derive an affine transformation between two frames by using normalized cross-correlation as the similarity measurement metric, which achieves one of the best results on CLUST 2015 2D point-landmark tracking currently.…”
Section: Introductionmentioning
confidence: 99%